2014
DOI: 10.1155/2014/467485
|View full text |Cite
|
Sign up to set email alerts
|

HPLC-UV Method Development and Validation of Potato Sprout Inhibitor 1,4-Dimethylnaphthalene Using Different Systems

Abstract: 1,4-Dimethylnaphthalene (1,4-DMN) is effective sprout suppressant used in potato stores in many countries in the world. High residue levels of this compound on the potatoes and in other environmental samples are considered for human health and environmental risks. Determination of the residue requires specific analytical methods to be developed and validated. In this study, HPLC-UV was selected for validating a separation method based on reversed phase for the analysis of 1,4-DMN using 2-methylnaphthalene (2-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…So, it is an important concern for storing harvested potatoes timely with proper sprout suppressants. The widely used CIPC has been reported to have some toxic effects on health as well as on environment due to their degraded by-products, uptake and residual effect on the tubers, low volatilization and less water solubility 15 , 16 , 26 , 33 . Residual effects of CIPC is noticed not only in the stored potatoes but also in the processed potato products 34 , 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, it is an important concern for storing harvested potatoes timely with proper sprout suppressants. The widely used CIPC has been reported to have some toxic effects on health as well as on environment due to their degraded by-products, uptake and residual effect on the tubers, low volatilization and less water solubility 15 , 16 , 26 , 33 . Residual effects of CIPC is noticed not only in the stored potatoes but also in the processed potato products 34 , 35 .…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that up to 45% of applied CIPC is persistent in the soil besides adhering to tubers 14 . It was observed that the CIPC residue in peel samples were fairly high about 15–85 mg/kg 15 , 16 . CIPC renders sprout growth by blocking the spindle formation during cell division 17 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Five replicate injections of 1 g/mL of a mixture of CIPC, IPC, and 3-CA were injected to measure the precision of the standard solution by calculating the relative standard deviation (RSD%) as described in recent study [19].…”
Section: Determination Of the Precision Of The Standard Solutionsmentioning
confidence: 99%
“…were estimated for three compounds as mentioned in recent study [19], applying two approaches including statistical regression of the low concentration range of 0.02-0.1 g/mL and ten replicate injections of mixed solution at the low concentration of 0.05 g/mL of CIPC, IPC, and 3-CA.…”
Section: Determination Of Lod and Loq The Lod And Loqmentioning
confidence: 99%